2020
DOI: 10.1017/s1368980019004877
|View full text |Cite
|
Sign up to set email alerts
|

Healthy nutrition in Germany: a survey analysis of social causes, obesity and socioeconomic status

Abstract: Objective:The obesity pandemic is an increasing burden for society. Information on key drivers of the nutrition cycle of (a) social causation, (b) biological causation and (c) health selection is vital for effective policies targeted at the reduction of obesity prevalence. However, empirical causal knowledge on (a) the social predictors of diet quality, (b) its impact on corpulence and (c) the socioeconomic consequences of obesity is sparse. We overcome the limitations of previous research and acquire comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…The occupational health check-ups did not achieve those with a significant increase in BMI at the 5-year follow-up. Elsewhere, it has been suggested to target the promotion of healthy diet to boys and men and people with low education [13].…”
Section: Discussionmentioning
confidence: 99%
“…The occupational health check-ups did not achieve those with a significant increase in BMI at the 5-year follow-up. Elsewhere, it has been suggested to target the promotion of healthy diet to boys and men and people with low education [13].…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, for example, the prevalence of being overweight or obese among adults was 54.0% according to the GEDA (GEDA, German Health Update) study from the Robert Koch Institute (a national public health institute in Germany) in 2014/2015, with men being affected more often than women [3]. Other personal aspects affecting obesity besides gender were low education and higher age according to Mader et al [4]. In addition, several German cohort studies have shown that the average weight in middle-aged populations increased slightly during recent years [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is of note that T2DM and dyslipidaemia are more prevalent in populations with low socioeconomic status (SES) [10] and this population is usually described as having poorer diet quality [11,12]. However, current literature is limited regarding the possible associations of overall diet quality, with the lipid profile in adults at highrisk of developing T2DM, as well as in individuals with low-SES.…”
Section: Introductionmentioning
confidence: 99%